The VW e-Race - Barreto, Beatriz Sales Marques (2019)
The world is in constant change, technology is evolving fast and, for that reason, organizations need to rapidly adapt and implement change in order to survive in this highly dynamic and competitive environment. Scholars have been investigating the reasons for strategic change and what are the capabilities that a firm needs to have in order to survive in an ever-changing world. In order to better illustrate these theories with a real-life example, I selected the case of Volkswagen and its late adoption of Electric Vehicles (EVs). The VW e-Race case intends to demonstrate how unprecedented change in the automotive industry impacted the German car maker. The company has been one of the leaders in diesel cars, but in what concerns the EVs’ business they seem to be getting behind their competitors. Volkswagen had a slow and weak entry in the EVs’ business with only two models being launched until 2018. Nonetheless, its diesel crisis, in late 2015, pressured them to re-organize the company’s strategy around electric cars. This case clearly demonstrates how, sometimes a firm needs to pass through a crisis in order to implement change. Moreover, it shows the relevance of organizational change and dynamic capabilities, for a company to sustain a competitive advantage in a changing environment.